The Roles of the Terms of Trade and the Real Exchange Rate in the Current Account Balance - Kose, Nezir; Unal, Emre (De Gruyter Poland Sp Z O O, 2024)
Turkey has been suffering from a persistent deficit in its current account for decades. The connection between the oil price, the real exchange rate, the terms of trade, industrial production, the foreign direct investments, and the current account balance was investigated by using the structural vector autoregression (SVAR) model. The exchange rate and industrial production accounted for the largest explanatory shares in the balance, according to variance decomposition, although their impacts diminished with time. The balance was also strongly influenced by the terms of trade. In the first few months, the oil price had a weak influence on the balance. However, its impact gradually grew over the course of the following periods. The impulse response functions showed that the exchange rate, industrial production, and terms of trade had a positive and significant effect on the current account balance in the short-term. Furthermore, the SVAR model was applied to the time frame before the COVID-19 pandemic. The results indicated that although the basic findings for the exchange rate and industrial production remained unchanged, their explanatory significance for the current account balance decreased. As a consequence, the country must formulate fiscal and monetary strategies that are advantageous in mitigating the impact of these variables on the balance.
Keywords: current account balance; real exchange rate; oil price; terms of trade; SVAR model; F1; F3